2019
DOI: 10.15252/embj.2018101153
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the seed: structural basis for supplementary micro RNA targeting by human Argonaute2

Abstract: microRNAs (miRNAs) guide Argonaute proteins to mRNAs targeted for repression. Target recognition occurs primarily through the miRNA seed region, composed of guide (g) nucleotides g2-g8. However, nucleotides beyond the seed are also important for some known miRNA-target interactions. Here, we report the structure of human Argonaute2 (Ago2) engaged with a target RNA recognized through both miRNA seed and supplementary (g13-g16) regions. Ago2 creates a "supplementary chamber" that accommodates up to five miRNA-ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
208
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(237 citation statements)
references
References 54 publications
25
208
4
Order By: Relevance
“…AGO2 is involved in the RNA-induced silencing complex, which facilitates the repressing or degrading of target mRNAs by miRNAs. 35 The subcellular location revealed that circFUT8 was mainly distributed in cytoplasm, and circFUT8 was specially enriched by RIP assay for AGO2, which strongly supports the hypothesis that circFUT8 may function as a miRNA sponge. The prediction of targeted miRNAs and several assays, such as pull-down assay, dual-luciferase reporter assay, and biotin-coupled miRNA capture assay, indicated that circFUT8 harbored the binding site with miR-570-3p.…”
Section: Discussionsupporting
confidence: 67%
“…AGO2 is involved in the RNA-induced silencing complex, which facilitates the repressing or degrading of target mRNAs by miRNAs. 35 The subcellular location revealed that circFUT8 was mainly distributed in cytoplasm, and circFUT8 was specially enriched by RIP assay for AGO2, which strongly supports the hypothesis that circFUT8 may function as a miRNA sponge. The prediction of targeted miRNAs and several assays, such as pull-down assay, dual-luciferase reporter assay, and biotin-coupled miRNA capture assay, indicated that circFUT8 harbored the binding site with miR-570-3p.…”
Section: Discussionsupporting
confidence: 67%
“…Because the seed region can be separated by up to 15 nucleotides from supplementary region, and only 2 GC supplementary base pairs can significantly increase target affinity, it cannot be excluded that a lot of supplementary sites were overlooked in previous studies. According to the miRBase, about 25% of human miRNAs contain �3 GC nucleotides within positions g13-g16, which pointed out how important is the findings of Sheu-Gruttadauria and colleagues [9]. Similar results were obtained by 2 other research groups that used a high-throughput analysis to uncover the rules of miRNA target recognition.…”
supporting
confidence: 55%
“…Many studies have shown a compensatory role of nucleotides beyond the canonical seed through supplementary pairing (Broughton et al, 2016;McGeary et al, 2019). One such supplementary pairing region involves position 13-16 of the miRNA ( Figure 5A) (Sheu-Gruttadauria et al, 2019). An involvement of supplementary seed pairing in the toxicity of K12-6-5p was unlikely as the sequence of K12-6-5p shared no identity with the modified backbone carrying the AGCAGC 6mer seed that corresponded to the 3-8 seed in K12-6-5p (bottom two sequences in Figure 5A).…”
Section: Mir-k12-6-5p Predominantly Targets Essential Survival Genes mentioning
confidence: 99%